Development of Evaluation Model for 3X3 Basketball Referee Performance in the People’s Republic of China - Zhou, Yang; Siriphan, Chanchai; Tongdecharoen, Wisute (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: The proficiency of basketball referees' judgment not only directly impacts the technical and tactical aspects of the sport but also significantly influences the development of good sportsmanship within teams. Consequently, basketball referees play a crucial role in promoting the advancement of modern basketball, aiming for higher standards in terms of speed, accuracy, and overall health. Therefore, this research aims to develop an evaluation model for 3X3 basketball referee performance in the People’s Republic of China. Materials and Methods: This study is a mixed-methods research. The participants of this study can be divided into the following four groups: (1) 288 referees from Chinese basketball were selected to participate in the questionnaire; (2) 7 experts were invited for in-depth interviews; (3) 19 experts were invited to participate in two rounds of Delphi studies; and (4) 9 experts were invited to discuss and confirm the evaluation index model for the officiating performance of Chinese three-on-three basketball referees. The data obtained from the questionnaire was analyzed using mean and standard deviation, while consensus data was analyzed using median and CV, with the set standard being median ≥ 3.50 and CV ≤ 0.25. Results: The evaluation index model for the officiating performance of Chinese three-on-three basketball referees consists of 2 first-level indicators from theoretical classification, which are: (A) Assessment and evaluation scores; (B) Training and recommendation scores, and also includes 5 second-level indicators and 19 third-level indicators. Conclusion: After expert discussion by the connoisseurship method, the evaluation model for 3X3 basketball referee performance was confirmed, and all indicators in the developed evaluation model can be preserved.